Prevalence of C7 level anomalies at the C7 level: an important landmark for cervical nerve ultrasonography. (March 2016) - Takeuchi, Mikinobu; Aoyama, Masahiro; Wakao, Norimitsu; Tawada, Yuka; Kamiya, Mitsuhiro; Osuka, Koji; Matsuo, Naoki; Takayasu, Masakazu
Background: Recently, various examination and intervention techniques using cervical nerve ultrasonography have been developed. The specific shapes of the C7 transverse process and vertebral artery in front of the C7 transverse process have become landmarks. Purpose: To determine the prevalence of anomalies and anomalous vertebral artery entrances at the C7 transverse process. Material and Methods: The records of patients who underwent plain or contrast-enhanced neck or cervical spine computed tomography (CT) were reviewed. The examinations were scored for the anomalous presence of anterior tubercles or cervical ribs as well as vertebral artery entrances in the C7 transverse process. The prevalence of anomalies was compared based on patient sex and age. Results: Evaluating the examinations from 2067 patients (1046 men; 1021 women), 1% of patients exhibited an anomalous presence of anterior tubercles, and 0.3% of patients displayed cervical ribs at the C7 transverse process. The prevalence of anomalies process was significantly higher in men aged less than 40 years than in older men ( P  < 0.001), whereas the prevalence was not higher in women aged less than 40 years than in older women. The prevalence of vertebral artery entry into the C7 transverse foramen was 0.6%. Conclusion: Although an anomalous vertebral artery entry into the C7 transverse foramen was rare, the prevalence of an anomaly at the C7 transverse process was higher in men aged less than 40 years. Therefore, we recommend performing CT in younger men before cervical nerve ultrasonographic intervention to avoid misinterpretations at the cervical level.